Nivel de intimidación escolar en adolescentes entre 13- 15 años de una Institución Educativa de Riohacha. (2022)
The author of this study set himself the general objective of describing the level of school bullying in adolescents between 13-15 years of age at the Remedios Catalina Amaya Institution of the Special and Cultural Tourist District of Riohacha. For this, it was necessary to implement a quantitative methodology, seeking to measure the objectives in a quantifiable way, likewise, there was a non-experimental and cross-sectional design; Regarding the population, 76 students of the educational institution participated in the study, whose ages ranged between 13 and 15 years of age; Taking into account that the participants were minors, the author requested the signing of an informed consent signed by their parents or guardians; the instrument used to achieve the objectives was the CIE-A School Bullying Questionnaire by Cuevas (2010).